Hippocampal subfield volume differences are independent of age in teenagers and young adults with Down syndrome: Neuroimaging: The medial temporal lobe in 2020. (7th December 2020) - Koenig, Katherine A; Oh, Se‐Hong; Stasko, Melissa; Lissemore, Emma; Roth, Elizabeth; Birnbaum, Anne; Scheidemantel, Thomas; Taylor, Hudson; Roizen, Nancy; Ruedrich, Stephen; Leverenz, James B; Costa, Alberto
Abstract: Background: Down syndrome (DS) leads to a range of well‐described physiological and neuroanatomical characteristics, including a disproportionate decrease in corrected sizes of the hippocampus [1]. In young adults with DS, we previously reported decreases in the size of bilateral CA1 and dentate gyrus in comparison to age‐matched controls [2]. Here we compare hippocampal subfield volumes in teenagers and young adults with DS to age‐matched healthy controls, and assess the relationship of volume differences to age. Method: Sample: 34 teenagers and non‐demented adults with DS (mean age (years) 24.5 ± 6.5, range 15‐35; 22 males) and 27 age‐matched healthy controls (HC; mean age (years) 24.9 ± 6.1, range 15‐36; 17 males). MRI: All participants were scanned under an IRB‐approved protocol on a Siemens 7T Magnetom scanner. Using a whole‐brain MP2RAGE (0.75mm 3 isotropic voxel size), hippocampal subfield volumes were calculated and corrected for intracranial volume using the Automated Segmentation of Hippocampal Subfields (ASHS) software (Figure 1). Linear regression used to assess group and age differences in the subiculum, CA1, CA3, dentate gyrus, tail and total volumes. Result: Individuals with DS had disproportionately smaller bilateral CA1, CA3, dentate gyrus, and total hippocampal volumes, all of which were significant for group but not for age (Table 1). Volume of the right tail was the only region that was significantly age‐dependent (0.0039) in the full sample. However, when broken down by group, this relationship was only significant in individuals with DS (r = ‐0.410, p < 0.0168), not in controls (r = ‐0.308, p < 0.1180). In the DS group alone, age did not have a significant effect on any other subfield volume. Conclusion: In agreement with previous reports, we find a disproportionate decrease in hippocampal volume in persons with DS, driven by CA1, CA3, and the dentate. Although individuals with DS show early neuropathology associated with dementia onset, the majority of subfield volumes were not associated with age in this sample of teenagers and young adults. This work was supported by Alzheimer's Association, Alana USA Foundation (Contract 200381), and the National Institute of Aging (P30 AG062428 01), with technical support by Siemens Medical Solutions.